2021
DOI: 10.3390/biom11121770
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization of Seed-Expressed LEA_4 Proteins Reveals Liquid-Liquid Phase Separation for LEA9 and for LEA48 Homo- and LEA42-LEA48 Heterodimers

Abstract: LEA proteins are involved in plant stress tolerance. In Arabidopsis, the LEA_4 Pfam group is the biggest group with the majority of its members being expressed in dry seeds. To assess subcellular localization in vivo, we investigated 11 seed-expressed LEA_4 proteins in embryos dissected from dry seeds expressing LEA_4 fusion proteins under its native promoters with the Venus fluorescent protein (proLEA_4::LEA_4:Venus). LEA_4 proteins were shown to be localized in the endoplasmic reticulum, nucleus, mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 100 publications
(172 reference statements)
1
12
0
Order By: Relevance
“…However, in the presence of a membrane surface, dehydrins can gain a partial helical structure [ 72 ]. The representative RsLEA_139 ( Figure 5 ) dehydrin was predicted to be highly disordered in the solution (97%), suggesting its possible involvement in liquid–liquid phase separation (LLPS), followed by proteinaceous condensates formation, similar to how it was recently experimentally confirmed for two Arabidopsis LEAPs predicted to be 100% disordered [ 35 ]. Therefore, nuclear desiccation-inducible RsLEA_139 might be involved in the LLPS-related dynamic assembly of nuclear compartments such as nuclear bodies and chromatin structures [ 73 ] as a part of gene expression regulation during desiccation in R. serbica .…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…However, in the presence of a membrane surface, dehydrins can gain a partial helical structure [ 72 ]. The representative RsLEA_139 ( Figure 5 ) dehydrin was predicted to be highly disordered in the solution (97%), suggesting its possible involvement in liquid–liquid phase separation (LLPS), followed by proteinaceous condensates formation, similar to how it was recently experimentally confirmed for two Arabidopsis LEAPs predicted to be 100% disordered [ 35 ]. Therefore, nuclear desiccation-inducible RsLEA_139 might be involved in the LLPS-related dynamic assembly of nuclear compartments such as nuclear bodies and chromatin structures [ 73 ] as a part of gene expression regulation during desiccation in R. serbica .…”
Section: Discussionsupporting
confidence: 55%
“…Most LEAPs are predicted to be intrinsically disordered proteins (IDPs) [ 31 , 35 ]. The flexible structure of IDPs imposes restrictions on their 3D structure determination, as can be evidenced by a low number of deposed IDPs in the Protein Data Bank (PDB) [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These proteins are able to weakly associate with themselves or RNA, resulting in the formation of a membraneless organelle. Ginsawaeng et al [ 5 ] studied several LEA proteins from Arabidopsis thaliana using a combination of bioinformatics and fluorescence microscopy to examine the localization and phase separation properties of these proteins. In terms of self-association, they found that some LEA proteins could form oligomers, and, most interestingly, LEA proteins LEA9 and LEA48 formed droplet structures, showing that they form LLPS condensates.…”
mentioning
confidence: 99%